Estudo da atividade antinoceptiva de β-amirina, um triterpeno pentaciclíco isolado de Protium heptaphyllum March. em modelos experimentais de dor - Oliveira, Cinthya Iamille Frithz Brandão de (2010)
The effects of pentacyclic triterpene β-amiryn and β-amyrin, isolated from resin of Protium heptaphyllum March. (Burseraceae), were preliminarily showed significant tested in models of nociception oral, and antinociceptives effects, guiding the search with this isolate in the investigation of their effects in models of orofacial pain induced by capsaicin or formalin and against capsaicin-induced corneal pain; thermal pain (tail immersion test in hot water and hot-plate) and in acetic acid 0,6%-induced visceral nociception in mice. Male Swiss mice (n = 8 per group) were pre-treated with β-Amyrin (10, 30, and 100 mg/kg, p.o.), morphine (5 mg/kg, s.c.) or vehicle (distlled water + 0,05% Tween 80), one hour before the capsaicin (20 μl, 1.5 μg) or formalin (20 μl, 1.5%) injection into the right vibrissa. β-Amyrin was also assessed on pain-related behavioral test (Eye-wiping) by topical application of capsaicin (20 μl, 1.5 μg) on to the mouse conjuctiva and the time (sec) that the animal spent in eye wiping was determined during a 10 min period. The triterpenoid demonstrated mostly a dose-unrelated antinociception in all the test models of nociception. Against the orofacial pain induced by capsaicin, β-Amyrin (30 e 100 mg/kg, p.o.) and morphine showed greater potency in reducing the nociceptive response. At the doses employed, the reductions were 81 and 90% to β-Amyrin and 97% for the morphine, respectively. Capsaicin nociception in orofacial test is accompanied by a localized thermal flare (measured by thermometry), which was significantly diminished by pretreatment of animals with β-Amyrin or L-NAME, an NOS inhibitor. In four weeks diabetic mice, capsaicin injected into vibrissa pad demonstrated a lesser degree of orofacial nociception compared to non-diabetics. In formalin test, both morphine and β-Amyrin showed significant naloxone reversible antinociception in both phases. However, β-Amyrin inhibited the second phase response, more prominently, at 30 mg/kg. The caliculated ED50 values for β-Amyrin and morphine were 16,44 mg/kg (CL 10,0 - 38,41) and 3 mg/kg (CL 2,5 - 5,0) in the first phase and 43,37 mg/kg (CL 30,52 - 39,30) and 3 mg/kg (CL 2,5 - 5,0) in the second phase, respectively. Co-administration of β-Amyrin and morphine at their respective ED50 dose levels failed to demonstrate any additive or potentiating effect on anti-nociception. However, at ED25 and ED12.5 dose-combinations exhibited an antinociception that equalled their ED50 combination effect, suggesting that by the use of β-Amyrin, the analgesic dose of morphine could be minimised to avoid its high-dose-associated side-effects. Similar to morphine, β-Amyrin significantly blocked the pain-related suppression of food intake in formalin test. β-Amyrin (30 and 100 mg/kg was also effective in increasing the thermal pain threshold in hot-water tail immersion test (but not in hot-plate test), and in reducing the acetic acid-induced writhes. The antinociception produced by 30 mg/kg β-Amyrin was significantly blocked in animals pre-treated with the respective antagonists capsazepine (5 mg/kg, s.c.), and naloxone (1 mg kg/kg, i.p.), indicating the involvement of capsaicin (TRPV1) and opioid receptors in its mechanism. Like morphine, β-Amyrin showed an inhibitory effect on intestinal transit, an effect reversed by pretreatment with nonseletive opióide antagonist, naloxona. These data indicate that β-Amyrin has the antinociceptive potential comparable to peripheral analgesia produced by morphine that could be explored further on its suitability in developing a non-opioid analgesic useful in pharmacotherapy of trigeminal and visceral pathologies.